2016
DOI: 10.1177/0023677216682771
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive technique for intrathecal administration of morphine in rats: practicality and antinociceptive properties

Abstract: The intrathecal (IT) route of administration represents a means to reduce the dose of morphine administered for analgesia, potentially minimizing interactions between opioid effects and experimental outcomes. Perceived technical difficulty, and previously described invasive methods, may limit its use. This report describes a minimally invasive technique for IT administration of morphine by direct transcutaneous lumbosacral puncture in rats; and assesses antinociceptive properties of morphine in anaesthetized r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Landmark in intrathecal injection is crucial to identify the correct level of injection. Previously described by Thomas AA, et al [5] identifications of the lumbosacral region can be achieved by positioning the rats in a sternal recumbent position, maximally bending the vertebrae. In our case, we identified the proposed level of L1-L2 by palpating the back region of the rat, corresponding to the linear region of L4-L5.…”
Section: Resultsmentioning
confidence: 99%
“…Landmark in intrathecal injection is crucial to identify the correct level of injection. Previously described by Thomas AA, et al [5] identifications of the lumbosacral region can be achieved by positioning the rats in a sternal recumbent position, maximally bending the vertebrae. In our case, we identified the proposed level of L1-L2 by palpating the back region of the rat, corresponding to the linear region of L4-L5.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 384 references were identified by electronic search; 338 full-text studies were evaluated in accordance with the eligibility criteria and 290 were excluded. Finally, 48 studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] complied with all the established eligibility criteria and were included in the study ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate intrathecal positioning can typically be confirmed via the tail-flick test, but this response does not occur every time. Dura mater puncture can also be confirmed by other characteristics, such as the formation of an "S" shape by the tail, by hind paw retraction, and occasionally by backflow of the CSF [14,15,20]. After injecting a drug, temporary motor paralysis also occurs, which is a sign of successful drug administration.…”
Section: Procedures Of Intrathecal Injection By Acute Needle Puncturingmentioning
confidence: 98%
“…Substantial experimental research and a review of the literature in human medicine have been reported [1,[8][9][10]. Numerous research studies have used the epidural [4,11,12] and intrathecal routes [13][14][15] in mice and rats; however, to the best of our knowledge, no review of the literature has discussed the delivery process, challenges, and application of these routes in rats and mice.…”
Section: Pain Reliefmentioning
confidence: 99%
See 1 more Smart Citation